Walla Walla City Ordinance No. 2. An Ordinance Defining Offenses and Fixing the Punishment Thereof, §27 (16 Aug., 1878). - (:unkn) unknown (My University, 1878)
No person shall carry any concealed weapons within the corporate limits of the City of Walla Walla, and any person convicted thereof shall be fined in any sum not less than five or more than twenty-five dollars;
Keywords: CARRY - CONCEALED